Multidiagnostic analysis of ultrafast laser ablation of metals with pulse pair - LUNNEY, JAMES (My University, 2010)
Copper targets are irradiated in the ablation regime by pairs of equal, time-delayed collinear laser pulses separated on a timescale going from 2 ps to 2 ns. The ablation plume is characterized by ion probe diagnostic, fast imaging, and temporally and spatially resolved optical emission spectroscopy. The variation in the ablation efficiency with the delay between the pulses is analyzed by measuring the ablation crater profile with a contact profilometer. The second laser pulse modifies the characteristics of the plasma plume produced by the first pulse and the ablation efficiency. The different mechanisms involved in double pulse ultrafast laser ablation are identified and discussed. The experimental findings are interpreted in the frame of a simple model of the interaction of the second pulse with the nascent ablation plume produced by the first pulse. This model yields consistent and quantitative agreement with the experimental findings predicting the observed experimental trends of the ablation depth reduction and ion yield increase with the delay between the pulses, as well as the characteristic timescale of the observed changes. The possibility of controlling the characteristics of the plumes produced during ultrafast laser ablation via an efficient coupling of the energy of the second pulse to the various ablation components produced by the first pulse is of particular interest in ultrafast pulsed laser deposition and microprobe analyses of materials
PUBLISHED
Keywords: Fluids and plasma physics; pulsed laser deposition; pulsed laser deposition and microprobe analyses; Nanoscience & Materials